EFFECT OF BIOXCELL AND TRIS CITRIC EGG YOLK EXTENDER ON POST THAW SEMEN QUALITY AND IN VIVO FERTILITY IN CROSS BRED JERSEY BULL - BEURA, D; MISHRA, P C; DAS, P; MOHANTY, D N; BARIK, A K; BISWAL, S S (The Indian Journal of Animal Reproduction, 2023)
Present investigation was carried out to compare the commercially available extender Bioxcell® withtris citric egg yolk (TEYG) extender for post thaw quality and in-vivo fertility of jersey Red Sindhi cross bredbulls (CBJ). Twenty four ejaculates of semen samples were collected from four fertile CBJ bulls (5-6 years) byartificial vagina maintained at 41 °C.Qualifying ejaculates (>60% motility) from each bull were divided into twoaliquots and diluted with TEYG or Bioxcell®extender. Diluted semen was cooled, equilibrated at 4°C for 4hrsand filled in 0.5ml straws. Straws were cryopreserved in liquid nitrogen for 24 hrs. and then thawed at 37°Cfor 30 seconds to assess post thaw motility (PTM), livability (PTL), plasma membrane integrity (HOSr), andpercent intact acrosome (PIA). For comparison of in vivo fertility cows were inseminated under field conditionand fertility rate was calculated on conception rate (CR) basis. The PTM, PTL, HOSr and PIA were found to be51.05 ± 0.25 and 51.82 ± .26, 56.47 ± 0.41 and 56.46 ± 0.42, 67.94 ± 0.46 and 67.99 ± 0.45 and 69.53 ± 0.52and 69.55± 0.52 in TEYG and Bioxcell® extender respectively. The C.R. recorded for TEYG was 53.20% whilein Bioxcell® extender it was 52.67%. It is inferred that Bioxcell® can be alternatively used for cryopreservationof bull semen with comparable post thaw sperm parameters with that of TEYG extender.
Keywords: TEYG; Bioxcell; Bull semen; Cryopreservation; Yolk free commercial semen extender